2018
DOI: 10.1016/j.jconrel.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Remote-loading of liposomes with manganese-52 and in vivo evaluation of the stabilities of 52Mn-DOTA and 64Cu-DOTA using radiolabelled liposomes and PET imaging

Abstract: Liposomes are nanoparticles used in drug delivery that distribute over several days in humans and larger animals. Radiolabeling with long-lived positron emission tomography (PET) radionuclides, such as manganese-52 (Mn, T½=5.6days), allow the imaging of this biodistribution. We report optimized protocols for radiolabeling liposomes with Mn, through both remote-loading and surface labeling. For comparison, liposomes were also remote-loaded and surface labeled with copper-64 (Cu, T½=12.7h) through conventional m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 39 publications
3
25
1
Order By: Relevance
“…Targets have been irradiated with 16-MeV protons or less, because of the desirable cross section between 6 and 20 MeV, illustrating production of 52 Mn with low-energy cyclotrons (29,30,(32)(33)(34). Several separation methods have been developed for the purification of 52g Mn and are summarized in Table 2 (35,36). Although further optimization of the purification chemistry is required, these purification strategies have enabled the availability of this nuclide for research use.…”
Section: Production Of 52 Mnmentioning
confidence: 99%
“…Targets have been irradiated with 16-MeV protons or less, because of the desirable cross section between 6 and 20 MeV, illustrating production of 52 Mn with low-energy cyclotrons (29,30,(32)(33)(34). Several separation methods have been developed for the purification of 52g Mn and are summarized in Table 2 (35,36). Although further optimization of the purification chemistry is required, these purification strategies have enabled the availability of this nuclide for research use.…”
Section: Production Of 52 Mnmentioning
confidence: 99%
“…Therefore, simple techniques that will allow to efficiently label an approved nanomedicine after the fabrication process will enable more frequent use of nanomedicine prescreening in patients. For example, remote loading of 52 Mn‐DOTA to liposomes enabled their radiolabeling for PET imaging without effecting their encapsulated materials or their external surface properties …”
Section: Deciding When To Use Nanomedicinementioning
confidence: 99%
“…A different approach towards radiolabelled liposomes using 52g Mn was published by Jensen et al In this comparative study, 52g Mn(II) and 64 Cu(II) were prepared as their DOTA chelates and used for both internal loading and surface labelling of liposomes. In vivo biodistribution studies with the 52g Mn‐labelled liposome preparations revealed that liposomes with internal 52g Mn‐loading had a longer plasma half‐life than their surface labelled counterparts.…”
Section: Manganese‐52g In Preclinical Researchmentioning
confidence: 99%
“…In vivo biodistribution studies with the 52g Mn‐labelled liposome preparations revealed that liposomes with internal 52g Mn‐loading had a longer plasma half‐life than their surface labelled counterparts. The authors concluded that the reduced blood plasma half‐live of the surface modified liposomes could result from insufficient in vivo stability of the radiometal‐DOTA chelates …”
Section: Manganese‐52g In Preclinical Researchmentioning
confidence: 99%